Conflict, transition and agency: Reconceptualising the process of learning to teach. (November 2021) - Steadman, Sarah
Abstract: This paper details a conceptual framework for the shared discussion of teacher learning and development constructed around concepts of conflict, transition and agency . Arising from ethnographic study conducted in three contrasting graduate-level teacher education routes in England, the research findings present the process of learning to teach as inevitably conflictive. The resulting conceptual framework provides both a framing for current theories on teacher learning and a tool for discussion among teacher educators and preservice teachers across different routes into teaching. In addressing concepts relevant to ongoing teacher development, the framework is useful beyond the preservice experience and the English context. Highlights: Becoming a teacher as recursive, emotional and inevitably conflictive. Conceptualisation of learning to teach around conflict, transition and agency . Pedagogical implications of conceptual framing.